Literary traditions of the Tamil Sangam and medieval period in the Christian marriage of the Tirunelveli Tamils - Samikkanu Jabamoney Ishak Samuel (Tanjong Malim, 2020)
Literary traditions of the Tamil Sangam and medieval period in the Christian marriage of the Tirunelveli Tamils by Samikkanu Jabamoney Ishak Samuel